Running performance has a structural basis - Weyand, P. G.; Davis, J. A. (The Journal of Experimental Biology, 2005)
The body sizes of highly adapted human and other mammalian runners vary in accordance with specific performance needs. Sprint specialists are relatively massive and muscular while endurance specialists are conspicuously limited both in body and in muscle mass. We hypothesized that the greater body masses of faster specialists are directly related to the greater ground support forces required to attain faster running speeds. Using human runners as a test case, we obtained mean values for body mass, stature and racing speed for the world's fastest 45 male and female specialists, respectively, over the past 14 years (1990-2003) at each of eight standard track racing distances from 100 to 10,000 m. Mass-specific ground support force requirements were estimated from racing speeds using generalized support force-speed relationships derived from 18 athletic subjects. We find a single relationship between mass, stature and event-specific ground support force requirements that spans the entire continuum of specializations and applies both to male and to female runners [body mass (kg)=mass-specific support force x stature2 (m) x a constant; N=16 group means, R2=0.97; where the ideal mass constant, D=10 kg m-2]. We conclude that running performance has a common structural basis.